A Case of Furuncle Treated with Homoeopathic Similimum (Homoeopathy for All, 2023)
Homoeopathy is a unique system of  medicine based on individualization  and symptom similarity of the  patient. It treats sickness of a man  as a whole and individualised  entity. Homoeopathy can help in the  treatment of various skin conditions,  as it can be seen from the case report  presented of a 21 years old girl who  was suffering from furuncle since  2 weeks and treated within 1 week  with Homoeopathic similimum  which was selected on the basis of  individualisation.
Keywords: Homoeopathy; furuncle; Individualisation; S. aureus